Ultrasound elastography findings in piriformis muscle syndrome - Demirel, Adnan; Baykara, Murat; Koca, Tuba Tülay; Berk, Ejder (Indian Journal of Radiology and Imaging, 2018)
Background: Piriformis muscle syndrome (PMS) is relatively less known and underestimated because it is confused with other clinical pathological conditions. Delays in its diagnosis may lead to chronic somatic dysfunction and muscle weakness. Objective: Here, we aimed to evaluate the diagnostic performance of the ultrasound elastography (UE) as an easy, less-invasive, and cost-effective method for early diagnosis of PMS. Materials and Methods: Twenty-eight cases clinically diagnosed as PMS at the outpatient clinic were evaluated by UE. The elastographic strain ratio was calculated by dividing the strain value of the subcutaneous fat tissue by the mean stress value of the muscle beneath. The diagnostic performances of the strain rate measures were compared using the receiver operating characteristic curve analysis. Results: Twenty-one (N = 21) cases were female, and seven (N = 7) of the cases were male. The mean age was 45 years (ranged 24–62 years). The strain rates of piriformis muscle (PM) and gluteus maximus (GM) muscles were significantly higher on the PMS-diagnosed side (P < 0.001). The cutoff value of UE strain ratio for the PM and GM were 0.878 [95% confidence interval (CI) 0.774–0.981] and 0.768 (95% CI 0.622–0.913), respectively, and the sensitivity and specificity values were, respectively, 80.95% and 85.71% for the PM, and they were, respectively, 85.71% and 66.67% for the GM. Conclusion: We showed that the muscle elasticity and tissue hardening increased on the problematic side both on PM and GM. UE may provide early diagnosis of PMS, thereby increasing the possibility of treatment with less invasive methods.
Keywords: Elastography; piriformis muscle syndrome; ultrasound